Effect of serum inflammatory markers on the prognosis of adult and pediatric patients with Guillain–Barré syndrome - Ethemoglu O; Calik M (Neuropsychiatric Disease and Treatment, 2018)
Ozlem Ethemoglu,1 Mustafa Calik2 1Department of Neurology, Harran University School of Medicine, Şanlıurfa, Turkey; 2Department of Pediatric Neurology, Harran University School of Medicine, Şanlıurfa, Turkey Objective: The aim of this study was to evaluate blood neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), C-reactive protein (CRP), and albumin levels for their prognostic value in adult Guillain–Barré syndrome (GBS-A) and pediatric Guillain–Barré syndrome (GBS-P) patients. Patients and methods: We retrospectively analyzed the medical records of 68 Guillain–Barré syndrome (GBS) patients (36 adults, 32 children) who were treated as inpatients at Harran University Faculty of Medicine, Neurology and Pediatric Neurology Departments. The pretreatment NLR, PLR, CRP, and albumin levels and Hughes scores at hospital admission, discharge, and third-month control were documented. Results: In GBS-A patients, the mean CRP and NLR levels at admission/discharge and third-month control were significantly higher, and the mean albumin level was significantly lower in the Hughes disability scale (HDS)≥3 group. In GBS-P group, the mean NLR level at third month was significantly higher in the HDS≥3 group. GBS-A patients had higher mean NLR, PLR, and CRP levels and lower mean albumin values than GBS-P patients. Both GBS-A and GBS-P patients had higher mean NLR, PLR, and CRP levels and lower mean albumin values than healthy controls. Only the albumin level of the GBS-A group was found to be a significant predictor of prognosis at discharge from hospital. Conclusion: NLR, CRP, and albumin levels in the GBS-A group and NLR levels in the GBS-P group may be helpful in predicting the prognosis of the disease. The albumin level of GBS-A patients is an independent risk factor for prognosis at discharge from hospital. Keywords: Guillain–Barré syndrome, albumin, neutrophil–lymphocyte ratio, platelet–lymphocyte ratio, C-reactive protein